Essays in Honor of Cheng Hsiao - Terrell, Dek (Advances in Econometrics Ser., 2020)
Including contributions spanning a variety of theoretical and applied topics in econometrics, this volume of Advances in Econometricsis published in honour of Cheng Hsiao.